Mathematical modeling of the process of ferrum removal in a biological reactor by bacteria Gallionella and Leptothrix - Prysiazhniuk, Olena; Prysіazhnіuk, Igor; Kvartenko, Alexander (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
This paper proposes a mathematical model for computer prediction of the process of biological deironing of groundwater in a bioreactor, taking into account the presence of two types of iron bacteria Leptothrix and Gallionella in groundwater while maintaining a constant filtration rate. An algorithm for a numerical-analytical method for solving the corresponding nonlinear boundary value problem for an inhomogeneous system of differential equations in partial derivatives of the first order has been developed. The developed model allows to use computer experiments to predict the change in time on the depth of contact loading of cleaning efficiency, distribution of bacterial biomass values ​​in both filtered water and in filter loading, mass of stationary and mobile matrix structures. Also, the proposed model allows to predict the duration of effective operation of the biological reactor of iron deironing between its washing.